Domain size engineering of CVD graphene and its influence on physical properties. (18th April 2016) - Mas'ud, Felisita Annisanti; Cho, Hyunjin; Lee, Taegeon; Rho, Heesuk; Seo, Tae Hoon; Kim, Myung Jong
Abstract: An electrochemical polishing pre-treatment and atmospheric pressure annealing were performed on copper foils in order to obtain large graphene domain sizes by the chemical vapor deposition method. The sizes were confirmed through scanning electron microscopy, optical microscopy and Raman spectroscopy, among other additional characterizations. The larger domain size was expected to improve the quality of the graphene but, on the contrary, the sheet resistance of the samples was found to increase for the larger domain size. We conclude that although the domain size is larger, the sheet resistance of graphene is more affected by the quality of the graphene interdomain itself.